Labour force sample survey Curacao 1990-1992 including first results 1993 (Central Bureau of Statistics WillemstadAN, 1994)
Contains an analysis of the results of the surveys held in the consecutive years 1990-1992 in Curacao, including a time series for the main results of 1988-1992.
DC